The relative efficacy of positively and negatively valenced road safety campaign messages in improving dangerous driving attitudes - Ben W. Morrison; Mark Sasaki; Natalie M.V. Morrison (Journal of Road Safety, 2020)
Dangerous driving is a social problem that results in serious injuries, fatalities, and significant economic costs. Extensive research has examined the efficacy of road safety campaigns in curbing dangerous driving, however, these investigations have largely focused on negatively valenced messages. Less attention has been paid to positively valenced examples, and the role of drivers’ motivations for dangerous driving in relation to message impact. One hundred sixty licensed drivers (female, n = 120; male, n = 30; other, n = 10) completed a questionnaire that measured their current driving behaviours and their motives for driving dangerously. Drivers then viewed one of two safe driving messages (either positive or negative in valence) and provided a gauge of message impact. Finally, looking to the future, participants completed a measure of planned driving behaviour. Results revealed differences across sex in drivers’ motivations to drive dangerously, as well as their planned behavioural change after viewing the safety messages. On average, participants recorded greater response efficacy and message acceptance, and lower message rejection in the positive message group, compared to the negative message group. Further, in a separate analysis of female-only drivers, a number motivators of dangerous driving were linked to message impact from safe driving campaigns. The findings suggest that, despite the traditional dominance of negatively valenced campaigns, there may be benefit in the use of positive campaigns, and further that motivators of dangerous driving can be linked to message impact from safe driving campaigns, supporting the case for a more targeted approach in campaign design.